Parkinson's Disease and Beyond A Neurocognitive Approach - Palermo, Sara; Stanziano, Mario; Morese, Rosalba (IntechOpen, 2019)
Parkinson's Disease and Beyond - A Neurocognitive Approach aims to bring together in a single publication the knowledge of diagnosis and characterization of the clinical and neuropsychological profile in Parkinson's disease. The strong impulse to research this topic has produced in recent years a large literature that documents the high level of complexity of the issue. Due to this complexity, a reasoned multidimensional analysis able to integrate expertise of different disciplines (neurology, neuropsychology, neuroradiology, and neuroscience) is necessary. This book offers an excellent synopsis of perspectives, methods, empirical evidences, and international references. It represents an extraordinary opportunity to target challenging unmet needs and to outline new horizons in Parkinson's disease research.